Promoting Communication Value and Worth in Economics of Chemical-Free Rice Learning - Theeranan Khantee; Apinya Anphanlam (Journal of Educational Issues, 2024)
This participatory action research’s goal was to investigate the manner in which rice grown without chemical additives is communicated as having value and worth. Data were gathered from local people through in-depth interviews, focus groups, agent interviews, questionnaires, surveys, observations, and documentary research. The findings of this study show that there are four different types of communication: group communication, individual communication, communication through mass media and social media, and community communication. This knowledge is either a benefit for organizing public campaigns or a clear invitation to farmers who want to switch to chemical-free farming and understand its significance.